Between mandatory vaccination and the COVID-19 pandemic: effects on the vaccination coverage trend in a province of Southern Italy: COVID-19 effect on vaccination trend - Genovese, Cristina; Pantò, Giuseppe; La Spina, Isabella; Tripodi, Paola; D'Amato, Smeralda; Facciolà, Alessio; La Fauci, Vincenza; Squeri, Raffaele (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Although vaccination is considered an extraordinarily effective and safe tool for the prevention of infectious diseases, from 2013 to 2016 CVs at national level showed a downward trend, falling well below the 95% threshold recommended by the WHO to limit the circulation of viruses and bacteria in the community and to obtain the so-called herd effect in addition to the protection of individual vaccinated individuals. The aim of the study was to assess vaccination coverage data following the introduction of Law 119/2017 and in like to COVID-19 pandemic the impact on vaccination coverage. Methods: The study was conducted from 1 October 2019 to 1 October 2022, using the OnVac programme. Results: The analysis of the coverage rates of hexavalent vaccination during the entire study period shows that there was an increase in vaccinations during the two-year period 2020-2021, followed by a drastic decrease down to values below 95%. where variable coverage was noted between the two genders with higher percentages in the female sex. Contrary to expectations, 2021 did not allow the recovery of the defaulting cohorts, with a drop in coverage much higher than in previous years (with values approaching the values of 2008), not only for polio, diphtheria and tetanus, but also for measles, mumps, rubella, chicken pox and HPV, effectively getting worse over the previous decade. Conclusions: immunization challenges need to be addressed to ensure that every child, adolescent or patient at risk is immunized, especially but not only for COVID-19.